1996
DOI: 10.1063/1.360930
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of zinc-blende GaN, AlN, and their alloys Ga1−xAlxN

Abstract: Articles you may be interested inWhispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots Appl. Phys. Lett. 102, 081105 (2013); 10.1063/1.4793653 Erratum: "Ab initio study of lattice vibration and polaron properties in zinc-blende AlxGa1−xN alloys" [J. Appl. Electronic and positron properties of zinc-blende structure of GaN, AlN, and their alloy Ga 1−x Al x N J. Appl. Phys. 93, 9730 (2003); 10.1063/1.1573739 Deposition factors and band gap of zinc-blende AlNThe electronic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(25 citation statements)
references
References 39 publications
2
18
1
4
Order By: Relevance
“…It is also found that the nature of bandgap for the full compositional range of Ga in Al 1−x Ga x N ͑0 Յ x Յ 1͒ is direct ͑E g ⌫−⌫ ͒. Our results are in agreement with the experimental ones, 23 and are in contradiction with the experimental 20,21 as well as theoretical 18,19,21,22 results. They are of the opinion that the bandgap of the compound is indirect at ͑⌫ − X͒ symmetry points.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…It is also found that the nature of bandgap for the full compositional range of Ga in Al 1−x Ga x N ͑0 Յ x Յ 1͒ is direct ͑E g ⌫−⌫ ͒. Our results are in agreement with the experimental ones, 23 and are in contradiction with the experimental 20,21 as well as theoretical 18,19,21,22 results. They are of the opinion that the bandgap of the compound is indirect at ͑⌫ − X͒ symmetry points.…”
Section: Resultscontrasting
confidence: 54%
“…Bandgap nature of Al 1−x Ga x N ͑0 Յ x Յ 1͒ is controversial. Experimental evidences 20,21 and theoretical calculations 18,19,21,22 suggest that the bandgap of Al 1−x Ga x N ͑0 Յ x Յ 1͒ is indirect for all concentration of Ga. While the experimental results of Ref.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…24,25 Other attributes of III-nitride systems are that their energy gaps can be varied over a wide range and these systems have high electron mobilities and heat conductivities and in addition, for example, GaN has a high breakdown voltage and a small dielectric coefficient. 7,26,27 The InGaN/GaN single and/or multiquantum wells have been used as active layers for blue lightemitting diodes and laser diodes. InGaN multiple quantum wells (MQWs) grown on sapphire substrates have been demonstrated and there are many reports on the optical investigation of InGaN/GaN quantum well structure.…”
Section: Introductionmentioning
confidence: 99%
“…3.5 para as respectivas massas efetivas dos buracos, obtemos os valores para os parâmetos de Luttinger do c-BN, os quaiS estão apre sentados na tabela 3.6, onde também inserimos os valores correspondentes a esses mesmos parâmetros para os compostos GaN e AIN, extraídos da referência [89]. É interessante notar que a medida que se aumenta a massa atômica do cátion, o composto exibe valores maiores para os parâmetros de Comparativamente aos estudos de defeitos e ímpurezas em Si, GaAs, GaP e outrOS semicondutores, aqueies realizados em BN estão em sua infancia, Apesar da importância tecnológica e em Física básica deste material, apenas recentemente alguns trabalhos mais detalhados sobre defeitos começaram a ser publicados.…”
Section: Estudo Do Nitreto De Boro Cúbico Através Do Método Flapwunclassified